Pengaruh Budaya Organisasi dan Lingkungan Kerja Terhadap Kinerja Karyawan PT. Bama Berita Sarana Televisi (BBSTV Surabaya) - Anis Watul Khasanah (BIMA : Journal of Business and Innovation Management, 2019)
PT. Bama Berita Sarana Televisi (BBSTV Surabaya) is a company engaged in television in Surabaya and found problems about employee performance. The purpose of the research was to determine the influence organizational culture and job environment on employee performance PT. Bama Berita Sarana Televisi (BBSTV Surabaya). Population and sample in this research taken 63 employees with questionnaire distribution method and using saturated sample technique and using regression analysis technique. Based of the results of the analysis shows the partially the organizational culture have a negative significant on employee performance BBST Surabaya with thitung (-2,153). Partially job environment have a influence positive significance on employee performance BBSTV Surabaya with Fhitung 13,715. Together with the organizational culture and job environment influence the employee’s performance. Between the two job environment variables most affect employee performance BBSTV Surabaya.